1993
DOI: 10.1103/physrevc.47.1170
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral interactions in the collision ofO16+238

Abstract: Inclusive and semiexclusive elemental production cross sections of projectilelike fragments emerging in the collision ' 0+ U at 110. 4 MeV have been investigated. Energy spectra and angular distributions of projectile residues with charge from Z =3 to Z = 8 have been measured. It has been found that, as expected, the dominant reaction mechanism in the peripheral collisions is a mass transfer from projectile to target mainly dominated by a transfer of an a particle. The in-plane coincidences between projectilel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The DWBA analysis of the inclusive data discussed in Ref. [1] showed that at the grazing angle (= 70') the PLF energy spectra were described by quite similar Q values and angular momentum distributions nearly independent of the PLF detection angle. However, the following remark concerns the quoted error on the Jacobian.…”
Section: Experimental Apparatusmentioning
confidence: 95%
See 4 more Smart Citations
“…The DWBA analysis of the inclusive data discussed in Ref. [1] showed that at the grazing angle (= 70') the PLF energy spectra were described by quite similar Q values and angular momentum distributions nearly independent of the PLF detection angle. However, the following remark concerns the quoted error on the Jacobian.…”
Section: Experimental Apparatusmentioning
confidence: 95%
“…As suggested in Ref. [1], other carbon isotopes are expected in the reaction, changing, consequently, the kinematic of the recoil target nucleus. Assuming that the carbon ejectile was equally populated by isotopes with mass number A between 11 and 14, a dispersion on the value of the Jacobian of 15% was evaluated.…”
Section: Experimental Apparatusmentioning
confidence: 96%
See 3 more Smart Citations